Pengembangan Media E-Comath untuk Meningkatkan Kemampuan Komunikasi Matematis Peserta Didik Kelas V dalam Materi Skala pada Denah - Fatimah, Siti Nur; Isrok'atun, Isrok'atun; Hanifah, Nurdinah (SJME (Supremum Journal of Mathematics Education), 2024)
Comics are a tool that can be used as a media to improve communication skills through the various graphic illustrations conined in them. In the realm of education, especially in mathematics lessons, comics can be used as a learning media that can improve student mathematical communication skills. In this research, researchers developed digital comic media or E-Comath (Electronic Comic Mathematics) in scale material on a floor plans in class V students at SD Negeri Sindang III through the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. In this research, the instruments used were interviews, media and material validation sheets, tests in the form of written questions, and student responsee questionnaires. The validation results show that the E-Comath is valid and suitable for use with an average media assessment percentage of 95,8% and an average material assessment percentage of 98,7% in the very good category. E-Comath media can also increase mathematical communication skills of 0,46                                        which is calculated using the N-Gain formula, and is included in the moderate improvement category, so it is effective to use. Apart from that, E-Comath media received a positive response  from students to be used as a learning media.